Perlindungan Hukum terhadap Anak di Bawah Umur dalam Perkara Tindak Pidana Narkotika - Hasan, Zainudin; Susanto, Ignasius Evan Fidel; Kenali, Fabia Prasetyo; Novita, Dessy; P, Reni Hasnila Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Narcotics crime is an extraordinary crime (extra ordinary crime) modus operandi is quite sophisticated and continues to experience changes to avoid tracking by law enforcement officials. This is the adult mode The latest thing to do is involve minors as couriers or delivery of drugs into the hands of users. The problem is the point attention is that when children are caught by officers they are immediately arrested became a suspect and was taken into custody. Even though children should be placed as a victim of the development of the big bookie mode in distributing drugs. The fact is that children are the perpetrators of the crime Drug criminals have not received maximum rights in the system juvenile criminal justice.